Hypermagnesemia and hyperphosphatemia are highly prevalent in patients with COVID-19 and increase the risk of death - Justyna Malinowska; Milena Małecka-Giełdowska; Diana Bańkowska; Kinga Borecka; Olga Ciepiela (International Journal of Infectious Diseases, 2022)
Objectives: Nonrespiratory manifestations of COVID-19 include endocrine disorders, among which are calcium-magnesium-phosphate homeostasis abnormalities, which seem to influence the disease severity and patient outcome. The aim of this study was to evaluate the prevalence and impact of calcium-magnesium-phosphate and vitamin D3 disorders on survival in patients hospitalized for COVID-19 depending on the severity of the disease and kidney function. Design or methods: The study was conducted between April 2020 and May 2021 at Central Clinical Hospital in Warsaw, Poland. A total of 146 patients who had tested concentration of at least one of the studied elements, estimated glomerular filtration ratio, creatinine levels, and blood saturation, and were diagnosed with COVID-19 disease were included in the analysis. Results: We found that hypermagnesemia was common and associated with a 1.5-fold increased risk of death in the whole cohort. Hyperphosphatemia also increased the risk of death, exactly 2.4-fold. Furthermore, we found a statistically significant association between increased mortality in the whole cohort and hypovitaminosis D3 (P <0.05). Serum creatinine concentration and estimated glomerular filtration ratio significantly correlated with serum magnesium and phosphate levels. Conclusion: Hypermagnesemia, hyperphosphatemia, and hypovitaminosis D but not hypocalcemia influence the mortality of patients with COVID-19. These parameters should be monitored routinely in this group of patients, especially in those with decreased kidney function.